2019
DOI: 10.3390/min9050319
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of White Metal in a NaCl-H2SO4 System under Environmental Conditions

Abstract: The effect of NaCl on the leaching of white metal from a Teniente Converter was investigated in NaCl-H2SO4 media under environmental conditions. The copper dissolution from white metal was studied using ferric ions in the range of 1–10 g/L, NaCl in the range of 30–210 g/L, and sulfuric acid in the range of 10–50 g/L. The test without NaCl produced a dissolution of 55%; through the addition of NaCl, the dissolution increased to nearly 90%. The effect of sulfuric acid on the copper dissolution was not significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Hence, the leaching kinetics of chalcocite in acidic ferric sulfate media has been extensively studied and reported that chalcocite dissolution occurred in two distinct stages (Eqs. 1, 2) (Bolorunduro, 1999;Miki et al, 2011;Castillo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the leaching kinetics of chalcocite in acidic ferric sulfate media has been extensively studied and reported that chalcocite dissolution occurred in two distinct stages (Eqs. 1, 2) (Bolorunduro, 1999;Miki et al, 2011;Castillo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The type of water quality depends on several factors, such as possible interactions of the elements dissolved in water, chemical agents, and equipment material used [41][42][43]. The use of seawater or saline water to leach copper ores concentrates or other products that contain copper is common in hydrometallurgy [41,44]. The positive effect of the saline water use on hydrometallurgical processes is the important reduction in freshwater consumption and the improvement of the process performance (kinetic and copper recovery).…”
Section: Water Scarcitymentioning
confidence: 99%
“…The excellent results reported with the addition of halides include the use of iodine in leaching copper and gold [45][46][47]. The successful use of chlorinated media has been widely reported with concentrates and other copper sulfide products [14,48,49].…”
Section: Introductionmentioning
confidence: 99%